HUBUNGAN ANTARA PENGETAHUAN PENDERITA TBC DENGAN KEPATUHAN DALAM KONTROL BEROBAT TBC DI PUSKESMAS NGORO KECAMATAN NGORO KABUPATEN MOJOKERTO - Triwibowo, Heri; Nurjubaidah, Siti (Jurnal Keperawatan Bina Sehat, 2012)
Lung tuberculosis disease is a chronic infectious disease caused by Mycobacterium Tubercolosis. This disease is a major public health problem in Indonesia. One way to prevent it by requiring a TBC patient to control TBC treatment regularly. And a risk factor for tuberculosis treatment failure is patient obedience in tuberculosis treatment control, obedience control while greatly influenced by the level of knowledge of the patient. This research do to know relationship between TBC patient knowledge with TBC control treatment in obedience at public Health Centers at Ngoro District Mojokerto Regency. The method used in this research is correlation research design. TBC patient population is TBC patient at Public Health Centers Ngoro District Mojokerto Regency. Total of samples is 24 patients with a sampling technique that is purposive sampling techniques. Independent variable is the level of knowledge TBC patient a bout of TBC disease and Dependent variable is obedience TBC control treatment. Data obtained by distributing questionnaires and observations in TBC patient Ngoro Public Health Centers Mojokerto Regency. The results of this research showed a significant relationship by using two-sample test kormogorov-Smirnov test with a significance value 0.017 <0.05. These results indicate H1 accepted, so there is a relationship between the level knowledge of tuberculosis patients with treatment in obedience at Public Health Centers Ngoro District Mojokerto Regency. This means the higher the level of knowledge of TBC patient, so the level of obedience in control treatment will increase. Role of health workers will be expected to increase knowledge of TBC patient about TBC disease, either by providing infomation about TBC disease at regular intervals.Keywords: Knowledge, Obidience, TBC disease.